2019
DOI: 10.29252/pcnm.9.2.42
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress in Intensive Care Units Nurses: A Cross-sectional Study

Abstract: Background: Occupational stress can have seriously negative effects on the physical, psychological, and economic dimensions of nurses working in the intensive care units (ICUs). Objectives: Thus, this study was conducted to determine occupational stress in nurses who work in ICUs. Methods: This cross-sectional study was carried out on 120 nurses in three hospitals in Kerman, southeastern Iran. Data were gathered by Socio-Demographic Information and Osipow Occupational Stress questionnaires. Results: The mean o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This study was conducted in three hospitals (Bahonar Hospital, Shafa Hospital, and Afzalipour Hospital) affiliated with the Kerman University of Medical Sciences. Each hospital has five ICUs (i.e., Covid-19, poisoning, internal wards (1 and 2), and neurology department) with a total number of 192 staff [ 22 ]. This study was conducted from March 2021 to January 2022.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted in three hospitals (Bahonar Hospital, Shafa Hospital, and Afzalipour Hospital) affiliated with the Kerman University of Medical Sciences. Each hospital has five ICUs (i.e., Covid-19, poisoning, internal wards (1 and 2), and neurology department) with a total number of 192 staff [ 22 ]. This study was conducted from March 2021 to January 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Nouroozi Kushali et al (2013) reported ICU nurses' levels of stress, anxiety and depression as 33, 33.9, and 30.8%, respectively. Torkaman et al (2019) describe this intensity from moderate to severe. If this stress is ignored, it will cause many problems for nurses, such as sleep disorders, digestive disorders, general health decline, decreased functioning, reduced quality of care, job burnout, and leaving the job (Poursadeghiyan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, people with high work stress are more likely to have work accidents (Moayed et al, 2015). Despite the fact that nursing itself is stressful, in some wards, this stress is even multiplied (Torkaman et al, 2019). Close observation of health care conflicts, patients' pain and suffering, delays in clinical decision-making for end-of-life patients, and the inappropriate use of medical resources expose ICU nurses to the highest level of occupational stress (Torkaman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation